The influence of financial literacy, education, and stress on investment fraud moderated by financial behavior in millenials: English - Surya, Joanita Maria; Abdurrahman, Abdurrahman (Institute of Computer Science (IOCS), 2025)
The aim of this research is to explore the influence of financial literacy (FL), financial education (FE), and financial stress (FS) on investment fraud (IF) moderated by financial behavior (FB) among Millennials in the Greater Jakarta Area (Jakarta, Bogor, Depok, Tangerang, Bekasi, and Cianjur).The study sample consists of Millennials residing in the Greater Jakarta Area. The research methodology employed a survey method using a Google Form with 174 respondents. Data collection took place from May 2024 to June 2024. The findings indicate that Millennials' FB is influenced by their levels of FL and FE. High levels of FS affect Millennials' FB. Millennials with good FL and FE are better equipped to avoid IF. Managerial implications suggest a need to enhance financial knowledge among Millennials through FE and internal training. Government initiatives should focus on providing accurate investment knowledge and enhancing investment regulations